향후 2년 이내의 위암 검진 이용 의도의 예측 요인 - 함명일; 최귀선; 계수연; 곽민선; 박은철; Hahm, Myung-Il; Choi, Kui-Son; Kye, Su-Yeon; Kwak, Min-Son; Park, Eun-Cheol (Journal of preventive medicine and public health, 2007)
Objectives : The purpose of this study was to identify the factors influencing the intention to have stomach cancer screening using the theory of planned behavior (TPB) in Korea. Methods : For this population-based study, 1,535 adult respondents (aged 40 to 70 years) were recruited using multi-stratified random sampling and a face-to-face administered questionnaire. This study was based on Ajzen's theory of planned behavior. Intentions were divided into three scenarios for fee payment in the next two years : (1) free of charge, (2) co-payment, and (3) full charge. Multiple linear regression was used to identify the factors influencing the intention to have stomach cancer screening. Results : Perceived behavioral control and attitude toward stomach cancer screening were significant predictors of the intention to have stomach cancer screening. However, subjective norm only influenced the intention to have stomach cancer screening with full charge in the next two years. Conclusions : The results suggest that attitude and perceived behavioral control are likely to contribute toward increasing the intention to have stomach cancer screening. Especially, perceived behavioral control is a good predictor. Because the study subjects were nation wide residents, the study results can be generalized.